2019
DOI: 10.1002/esp.4630
|View full text |Cite
|
Sign up to set email alerts
|

An erosional origin for drumlins of NW Poland

Abstract: Drumlins are landforms essential to understanding of ice sheet movement over soft beds, sediment transport along the ice/bed interface, and the formation of a wide range of glacial deposits. Although investigated more than any other glacial landform, the origin of drumlins remains contentious. Using high‐resolution LiDAR imagery and field data, we investigate the geomorphology and internal composition of one of the biggest drumlin fields in the North European Lowland. The Stargard drumlin field consists of ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 148 publications
(249 reference statements)
11
33
0
Order By: Relevance
“…The results of the present study are consistent with the erosional origin hypothesis of Stargard drumlins by Hermanowski et al (). Although there is no obvious systematic relationship at the scale of the entire study area between the location of drumlins and the groundwater flow patterns and fluxes, such correlation is apparent in the south‐eastern part of the study area.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The results of the present study are consistent with the erosional origin hypothesis of Stargard drumlins by Hermanowski et al (). Although there is no obvious systematic relationship at the scale of the entire study area between the location of drumlins and the groundwater flow patterns and fluxes, such correlation is apparent in the south‐eastern part of the study area.…”
Section: Discussionsupporting
confidence: 94%
“…Our numerical simulation comprising a drumlin field offers a possibility to consider drumlin formation in the context of groundwater flow dynamics. In the parallel study of SDF, Hermanowski et al () documented the internal composition of several drumlins and analyzed the spatial characteristics of over 1,300 individual drumlins together with the geomorphological pattern of the entire drumlin field. Based mainly on the occurrence of diverse and from place to place different deposits (various till facies and sorted sediments) and their structural arrangements (undeformed to heavily glaciotectonized; geological contacts truncated by landform surfaces), it was concluded that the drumlin deposits mainly predate the drumlinizing event.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations